Osmotic Demyelination Syndrome due to Severe Hyponatremia Mimicking Hypoxic Encephalopathy - Wicke, Felix; Moreitz, Sasha; Weidauer, Stefan (Fortschritte der Neurologie · Psychiatrie, 2017)
Hyponatremia and its rapid correction is a well-known cause of osmotic demyelination most commonly affecting the pons. We report on a case of severe hyponatremia likely due to psychogenic polydipsia resulting in hypotonic hyperhydration with resulting cortical laminar necrosis on initial imaging, mimicking hypoxic brain damage. Pontine myelinolysis became apparent on follow-up imaging, illustrating the diagnostic challenges of extrapontine manifestations of severe hyponatremia.
Keywords: osmotic demyelination syndrome; central pontine myelinolysis; hyponatremia; cortical laminar necrosis